Digital cultural heritage - Kremers, Horst (Springer, 2020)
This book provides an overview of various application spheres and supports further innovations needed in information management and in the processes of knowledge generation. The professions, organizations and scientific associations involved are unusually challenged by the complexity of the data situation. Cartography has always been the central field of application for georeferencing digital cultural heritage (DCH) objects. It is particularly important in enabling spatial relation analysis between any number of DCH objects or of their granular details. In addition to the pure geometric aspects, the cognitive relations that lead to knowledge representation and derivation of innovative use processes are also of increasing importance. Further, there is a societal demand for spatial reference and analytics (e.g. the extensive use of cognitive concepts of
9783030151980
Keywords: Hardcover; Softcover / Geowissenschaften/Geografie; Geographical information systems; Cultural heritage; Multimedia systems; Geography; Digitalisierung; Digital Humanities; Kulturerbe